2013
DOI: 10.1111/aeq.12027
|View full text |Cite
|
Sign up to set email alerts
|

Political Mothering: Latina and African American Mothers in the Struggle for Educational Justice

Abstract: This article explores the process and impact of women organizing for educational justice in Northern California by documenting the efforts of a committed group of mothers who sought to address the disproportionate underachievement of Latino and African American students within their city's high school. Using a combined methodology of ethnography and participatory action research, this article illustrates the power of converting racial and social identities into a political strategy while constructing new narra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Studies have shown that, as they attempt to protect their families and communities, mothers sometimes redefine motherhood as collective caring involving grassroots activism that seeks to challenge structural inequalities and injustices. Conceptualized as political mothering (Fuentes 2013; Pardo 1990), activist mothering (Naples 1998), or motherhood-based activism (Edmonds-Cady 2009), these practices transform motherhood from a private identity into a basis for collective and politicized mobilizing and organizing. As Bourdieusian scholars would argue, women engaged in political mothering collectively challenge the “rules of the game” that seem unjust.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that, as they attempt to protect their families and communities, mothers sometimes redefine motherhood as collective caring involving grassroots activism that seeks to challenge structural inequalities and injustices. Conceptualized as political mothering (Fuentes 2013; Pardo 1990), activist mothering (Naples 1998), or motherhood-based activism (Edmonds-Cady 2009), these practices transform motherhood from a private identity into a basis for collective and politicized mobilizing and organizing. As Bourdieusian scholars would argue, women engaged in political mothering collectively challenge the “rules of the game” that seem unjust.…”
Section: Resultsmentioning
confidence: 99%
“…Scholars have richly documented how mothers, under various circumstances, have broadened their understandings of motherhood as collective caring, prompting them to confront the structural causes of inequalities and injustice threatening the welfare of their families or communities. Conceptualized as political mothering (Fuentes 2013; Pardo 1990), activist mothering (Naples 1998), or motherhood-based activism (Edmonds-Cady 2009; Taylor 1997), these practices transform motherhood from a private identity into a basis for collective and politicized mobilizing and organizing. Examples include activism that confronts state violence (e.g., the Mothers of the Plaza de Mayo), resists institutionalized racism (e.g., the Welfare Rights Movement), or challenges environmental or educational injustice (e.g., the Mothers of East LA).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Fuentes (2013) describes the concept of “political mothering” in her piece on Latina and African American mothers and their struggles for educational justice. While I would not call Esperanza’s mentoring of her sons and other Latinas as actively “political,” I would say that Esperanza was taking on a role of advocacy and leadership that was unusual, probably extraordinary, and possibly revolutionary for the time and place of 1950s Albuquerque.…”
Section: Padilla Testimoniosmentioning
confidence: 99%
“…Similarly, Esperanza actively used the relationships within her community to support women in their efforts to improve their skills and thus be stronger women for their families. Esperanza, by her actions, was embodying many of the concepts of the feminization of labor, namely, “women’s political activism, community work, and mothering as a form of reproductive labor” (Fuentes, 2013, p. 309).…”
Section: Padilla Testimoniosmentioning
confidence: 99%
“…Existen además algunas experiencias donde se han llevado a cabo estudios etnográficos de carácter colaborativo conectados de alguna manera con procesos de IAP, ya sea como etapa previa o posterior al desarrollo de los mismos. Encontramos ejemplos relacionados con procesos de patrimonialización (Hollowell y Nicholas 2009;Pyburn 2009), en producciones artísticas (Friedman 2013), o en los campos de la edu- cación (Villenas 2007;Van Sluys 2010;Fuentes 2013;García, A. et al 2015) y de la salud (Goepp et al 2008;Nugus et al 2012;Varcoe et al 2013;Gorli et al 2015;Oye et al 2015).…”
Section: Investigaciones Participativas Y Etnografías Colaborativas ¿unclassified